Effects of curcumin and tartrazine food colorants on biochemical and histochemical parameters in female sprague dawley rats - Shakoor, Sadaf (2019)
Food color is the first characteristic perceived by the human senses in food and food products. Almost all foods have food color from raw agricultural commodities to finished products. Incorporation of food colors (tartrazine and curcumin) could affect the healthy physiological system leading to changes in hematology, biochemistry and enzymatic activity. There are various undesirable products generated from endogenous aerobic metabolism such as reactive oxygen species (ROS). Generally, they create toxicological burden on human being. In order to investigate the effect of oral administration of tartrazine and curcumin for 15, 30 and 45 days; Doses were selected based on the acceptable daily intake (ADI) recommended by FDA. Doses were converted into animal equivalent dose; 9.6 and 96 (high) mg/kg/b.w/day for tartrazine, 3.8 and 38.6mg/kg/b.w/day for curcumin. Proximate analysis and phytochemicals screening of feed containing food colors were analyzed before conducting animal study. Through qualitative and quantitative analyses, phytochemicals such as saponins, glycosides, alkaloids, flavonoids, tannin, carbohydrates and phenolics were present in feed samples. Blood samples were collected for analysis of biochemical parameters i.e liver enzymes, renal functions, lipid profile, antibody response to sheep red blood cells (RBCs), reactive oxygen species (ROS), minerals status, antioxidants vitamins, thyroid and reproductive hormones. Organs and gut were collected for histopathology, and microbiota evaluation. Results revealed that total oxidants level was significantly increased in HT30 and non-significantly high in all treatment groups of 30 and 45 days. Whereas total antioxidants level was significantly decreased in HT 45. Elevations of arylestrase were seen in HT15, LT 45, HT45 and HC 45. The present study showed that curcumin and tartrazine significantly (P≤ 0.05) decreased the concentration of vitamin C in plasma of all groups of 30 days, HT45 and HC45 whereas increased the level of vitamin E in plasma of HT30, HC30, LT45 and HC45. Furthermore, WBCs were significantly higher in LT30 and HT30 while consumption of curcumin and tartrazine showed significant (P≤ 0.05) low level in MCV of the 30- and 45-days groups. Neutrophils were significantly increased in LT30 and HT30. High level of ALT was noted in all groups after 45 days. A significant increment was observed in the level of AST in HT45, LC45 and HC45 group. Besides, IgG, IgM and overall antibody GMT at 45 days were significantly (P≤ 0.05) increased. In addition, BUN (blood urea nitrogen) level was increased in LT30, HT30 LT45, HT45, and HC45 respectively while high level of creatinine was noted in HT15 and HT45. Lower level of bilirubin was seen in HT30, LC30, HC30 and all treatment groups of 45 days. Triglycerides was significantly high in treated group after 15 days, HT45 and HC45 respectively Tartrazine and curcumin significantly decreased the iron level of plasma in HT30, HC30, LT45, HT45, LC45 and HC45 group. Whereas, copper level was significantly high in LT15, HT15 and LT30 group. Iron level in rat liver was significantly high in LT30 verses HT30. Curcumin and tartrazine have decreased the zinc level in all treated groups of 45 days as compared to control. Oral administration of tartrazine was increased the sodium level of liver in HC15 and HC45 compared to LC15 and LC45. T4 level was significantly (P≤ 0.05) increased in HT15 and non-significantly low in HT30. Concentration of estrogen was low in the HT30 and HC30; non significantly high in all groups of 45 days. Low concentrations of FSH were found in LT30, HT30, LT45, and HT45 treatment groups compared to control, LT vs HT and LC vs HC at 15, 30 and 45 days were non significantly different. In addition, the histopathological examination of liver showed that pigment deposition in the portal canal and congested blood vessels accompanied by hemorhages in hepatic vein in animals given high tartrazine. Microscopically, kidney of treated group revealed acute degeneration and dilatation of glomerular capillaries, tubular necrosis, epithelial damage, chronic degeneration and dilatation of glomerular capillaries and severe degeneration and dilatation of glomerular capillaries. Histological changes in intestine treated with tartrazine for 30 and 45 days showed partial damaged degenerated mucosal epithelial cells, disrupted intestinal mucosal and epithelial tissue damage. Less mature graafian follicles and shrunken ovarian follicle, degenerated oocyte, degenerative and shrunken ovarian follicle, atrophy of ovarian follicle in ovary of all treated group with tartrazine and curcumin. Treated groups showed atropic thyroid follicles, congestion of thyroid follicles, dark black thyroid nuclei, nodular thyroid gland and hyperplasia of thyroid follicles. Furthermore, the gut microbiota was modified by the consumption of tartrazine and curcumin in female albino rats. Total bacterial count (TBC) obtained from tartrazine treated group significantly increased the number of pathogenic microorganisms (Saprophyticus, Pepto streptococci, S. pyogenes, Salmonella, E. coli and H. Pylori) compared to control. Tartrazine increased susceptibility to infectious diseases whereas curcumin increased the good organism and maintained the normal gut microflora (Lactobacillus and Epidermidis). In conclusion, the present study provided the evidence that severe changes in blood biochemistry, liver and kidney function test, minerals profile, antioxidant vitamins, hormones, alteration in histopathological and microbiological changes occurred at the ADI and high doses of tartrazine as compared to curcumin. Lower doses of these colors should be considered for food and pharmaceutical applications. The study showed that the ADI and doses up to 10 times higher than ADI showed negative effects on antioxidant level. Therefore, this study exhibited the importance of using appropriate doses of food colors (tartrazine and curcumin) for the utilization in different processed food products.